The Role of Consumer Trust in Sustainability in Increasing Interest in Purchasing Environmentally Friendly Products - Ernawati Ernawati; Lutfi Kausar Rahman; Erna Susanti; Anatia Agusti; Annisa Desty Puspatriani (Lembaga Pengembangan Kinerja Dosen, 2025)
This study explores the role of consumer trust in sustainability as a key factor influencing interest in purchasing environmentally friendly products. Despite increasing environmental awareness, many consumers remain hesitant to take action due to skepticism, perceived risk, and uncertainty about product authenticity. A systematic review of international literature (2020–2025) identifies five core trust dimensions: integrity, transparency, credibility, behavioral consistency, and long-term commitment. These dimensions shape consumers’ evaluations of green product claims and influence their willingness to engage in sustainable consumption. To explain the psychological mechanisms at work, the study integrates multiple theoretical perspectives: the Theory of Planned Behavior (TPB) emphasizes attitudes, subjective norms, and perceived control; Trust Theory explains how reliability and honesty reduce perceived risks; Signaling Theory clarifies how credible environmental communication influences consumer belief; and the Value-Belief-Norm (VBN) Theory connects personal values to pro-environmental actions. By synthesizing these frameworks, the analysis positions trust not merely as a mediating factor but as a foundational driver that enables the translation of positive environmental attitudes into actual green purchasing behavior. The findings underscore that businesses must move beyond superficial eco-friendly messaging to implement verifiable and consistent sustainability practices. This includes transparent reporting, third-party certification, and active stakeholder engagement. Policymakers also have a critical role in regulating misleading environmental claims and enforcing penalties for greenwashing, thereby protecting consumers and ensuring fair competition. Strengthening trust through these measures can help close the persistent gap between pro-environmental intentions and real-world purchasing actions. Overall, this study provides actionable insights for marketers, sustainability strategists, and regulators, highlighting that consumer trust is the cornerstone of sustainable market transformation. By cultivating trust, stakeholders can encourage environmentally responsible behavior at scale and contribute to long-term ecological well-being.